The Implementation of Realistic Mathematics Learning Approach for Function Topic in Class VIII SMP Negeri 1 Sungai Lala - Sudarmono (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2021)
This research is research on developing learning tools and applying Realistic Mathematics Learning (PMR) with the material Function. In the initial research, it appears that the teacher is still not maximally teaching according to the syntax or PMR steps. This is because the teacher does not understand the PMR learning tools that the teacher has just obtained, but the teacher has understood them in the next meeting. Students/students also have problems understanding the syntax of learning steps. This apparent difficulty is because students also get a different learning approach than usual. It is also seen that students have difficulty expressing their ability to read pictures or read problems. The researcher applies a modified four-dimensional model Thiagarajan, Semmel, and Semmel to produce relevant teaching materials. The teaching materials obtained consisted of (1) lesson plans, (2) teacher guidelines, (3) student books, (4) student activity sheets, and (5) learning outcomes tests. The experiment results found that the realistic mathematical approach was effective in functional learning in class VIII students of SMPN 1 Sungai Lala, Riau Province.